A Bending Willow Tree: A Japanese (Morita Therapy) Model of Human Nature and Client Change - Ishiyama, Ishu (Canadian Journal of Counselling and Psychotherapy, 2007)
Japanese Morita therapy are discussed to highlight its culturally and theoretically unique perspectives on human nature and client change: (a) theory of the shinkeishitsu (nervous) trait, (b) multiple-dimensional model of causes and treatment of shinkeishitsu neurosis, (c) theory of mental attachment, (d) reframing anxiety into constructive desires, (e) emphasis on action taking and experiencing, (f) restoration of balance in mental activities and attentional focus, (g) four-stage residential Morita therapy, and (h) counsellor contribution to client suffering and symptom aggravation. Eight examples are given to illustrate Moritian intervention responses.